Health Literacy and Outcomes of a Community-Based Self-Help Intervention: A Case of Korean Americans With Type 2 Diabetes. Issue 3 (May 2020) - Kim, Miyong T.; Kim, Kim B.; Ko, Jisook; Murry, Nicole; Xie, Bo; Radhakrishnan, Kavita; Han, Hae-Ra
Abstract : Background: Although scientific reports increasingly document the negative impact of inadequate health literacy on health-seeking behaviors, health literacy's effect on health outcomes in patients with diabetes is not entirely clear, owing to insufficient empirical studies, mixed findings, and insufficient longitudinal research. Objective: The aim of this study was to empirically examine underlying mechanisms of health literacy's role in diabetes management among a group of Korean Americans with Type 2 diabetes mellitus. Methods: Data from a randomized clinical trial of a health literacy-focused Type 2 diabetes self-management intervention conducted during 2012–2016 in the Korean American community were collected at baseline and at 3, 6, 9, and 12 months. A total of 250 Korean Americans with Type 2 diabetes participated (intervention, 120; control, 130). Participants were first-generation Korean American immigrants. Health literacy knowledge was measured with the original Rapid Estimate of Adult Literacy in Medicine and the diabetes mellitus-specific Rapid Estimate of Adult Literacy in Medicine. Functional health literacy was measured with the numeracy subscale of the Test of Functional Health Literacy in Adults and the Newest Vital Sign screening instrument, which also uses numeracy. Primary outcomes included glucose control and diabetes quality of life. Multivariate analyses included latent variable modeling. Results: A series of path analyses identified self-efficacy and self-care skills as significant mediators between health literacy and glucose control and quality of life. Education and acculturation were the most significant correlates of health literacy. Discussion: Despite inconsistent findings in the literature, this study indicates that health literacy may indirectly influence health outcomes through mediators such as self-care skills and self-efficacy. The study highlights the importance of health literacy, as well as underlying mechanisms with which health literacy influences processes and outcomes of diabetes self-management.